Acute Inflammatory Diseases of the Central Nervous System After SARS-CoV-2 Vaccination. Issue 1 (21st January 2023) - Francis, Anna G.; Elhadd, Kariem; Camera, Valentina; Ferreira dos Santos, Monica; Rocchi, Chiara; Adib-Samii, Poneh; Athwal, Bal; Attfield, Kathrine; Barritt, Andrew; Craner, Matthew; Fisniku, Leonora; Iversen, Astrid K.N.; et al.
Abstract : Background and Objectives: Acute inflammatory CNS diseases include neuromyelitis optica spectrum disorders (NMOSDs) and myelin oligodendrocyte glycoprotein antibody–associated disease (MOGAD). Both MOGAD and acute disseminated encephalomyelitis (ADEM) have been reported after vaccination. Consequently, the mass SARS-CoV-2 vaccination program could result in increased rates of these conditions. We described the features of patients presenting with new acute CNS demyelination resembling NMOSDs or MOGAD within 8 weeks of SARS-CoV-2 vaccination. Methods: The study included a prospective case series of patients referred to highly specialized NMOSD services in the UK from the introduction of SARS-CoV-2 vaccination program up to May 2022. Twenty-five patients presented with new optic neuritis (ON) and/or transverse myelitis (TM) ± other CNS inflammation within 8 weeks of vaccination with either AstraZeneca (ChAdOx1S) or Pfizer (BNT162b2) vaccines. Their clinical records and paraclinical investigations including MRI scans were reviewed. Serologic testing for antibodies to myelin oligodendrocyte glycoprotein (MOG) and aquaporin 4 (AQP4) was performed using live cell–based assays. Patients' outcomes were graded good, moderate, or poor based on the last clinical assessment. Results: Of 25 patients identified (median age 38 years, 14 female), 12 (48%) had MOG antibodies (MOGIgG+), 2 (8%) had aquaporin 4 antibodies (AQP4IgG+), and 11 (44%) had neither. Twelve of 14 (86%) antibody-positive patients received the ChAdOx1S vaccine. MOGIgG+ patients presented most commonly with TM (10/12, 83%), frequently in combination with ADEM-like brain/brainstem lesions (6/12, 50%). Transverse myelitis was longitudinally extensive in 7 of the 10 patients. A peak in new MOGAD cases in Spring 2021 was attributable to postvaccine cases. Both AQP4IgG+ patients presented with brain lesions and TM. Four of 6 (67%) seronegative ChAdOx1S recipients experienced longitudinally extensive TM (LETM) compared with 1 of 5 (20%) of the BNT162b2 group, and facial nerve inflammation was reported only in ChAdOx1S recipients (2/5, 40%). Guillain-Barre syndrome was confirmed in 1 seronegative ChAdOx1S recipient and suspected in another. Discussion: ChAdOx1S was associated with 12/14 antibody-positive cases, the majority MOGAD. MOGAD patients presented atypically, only 2 with isolated ON (1 after BNT162b2 vaccine) but with frequent ADEM-like brain lesions and LETM. Within the seronegative group, phenotypic differences were observed between ChAdOx1S and BNT162b2 recipients. These observations might support a causative role of the ChAdOx1S vaccine in inflammatory CNS disease and particularly MOGAD. Further study of this cohort could provide insights into vaccine-associated immunopathology.